PERCEPTION OF KNOWLEDGE AND UNDERSTANDING TOWARDS TEAM WORK EFFICIENCY IN THE ELECTRONIC PARTS MANUFACTURING INDUSTRY - สุจันทรา บุณริสาก์; กุณฑลบุตร ชนงกรณ์ (RMUTT Global Business and Economics Review, 2016)
The purposes of this study the factors influencing the perception of knowledge and understanding on team work efficiency in the electronic parts manufacturing industry. The samples were 389 participants who work in the electronic parts manufacturing industry, which were selected by purposive sampling. The research instrument used was the questionnaire related to the perception of knowledge and understanding towards team work efficiency, and the reliability of the instrument was 0.914. Statistics used for data analysis included Frequency, Percentage, Mean, Standard Deviation, and Multiple Linear Regression Analysis at a significance level of 0.05. The results revealed that the most important factors influencing the perception of knowledge and understanding on team work efficiency in the electronic parts manufacturing industry included organizational culture, compliance with the companies’ rules, and the change of organization design to match with the current situation, which had the coefficients at 0.641. The second important factors were leadership of head staff, comprising justice, successful team building, and appropriate job assignment to match employees’ capability, which had the coefficients at 0.384. The last important factor was corporate communication by providing the right news and information while reducing the conflicts among coworkers, which had the coefficient at 0.145.